Peran Otonomi Daerah Dalam Membangun Perekonomian Kabupaten/Kota di Indonesia - Kurniawan, Adji (Universitas Sang Bumi Ruwa Jurai, 2024)
This handover of affairs from the central government to the regions was clarified again with the promulgation of Law Number 23 of 2014 concerning Regional Government, but the impact This regional autonomy is not in line with the wishes of the constitution. Because inequality and economic policies between the center and regions or with surrounding areas result in the process of improving the economy being hampered and will even give rise to poverty trends. For this reason, the problems in this research discuss aspects of regional autonomy strategies in developing and building a good regional economy. The research method used is normative juridical research which is based on literature review and applicable laws and regulations. The prospect of regional autonomy for regional economic development can be implemented through the role of regional government as an entrepreneur, facilitator, coordinator and stimulator for the community to participate in improving the regional economy. To support this, there are regional autonomy strategy efforts that can be carried out by regional governments, namely through business development strategies, human resource development and community development